New Scheduling Rule Improves Pipeline Efficiency - Cafaro, Vanina (2011)
A new rule prioritizing product delivery to the eligible terminal closest to the one being currently served reduces total accumulated idle volume by about 40% and decreases the number of cut operations. Different priority arrays lead to different delivery schedules, strongly affecting cost-efficiency of the solution achieved. Prioritizing nearest-to-refinery terminals, for instance, may reduce the total volume of segments stopped, but the number of stripping operations will surely increase. Prioritizing the farthest terminals, however, may increase the number and volume of pipeline stoppages.